IMPLEMENTASI DESIGN THINKING DALAM PERANCANGAN USER INTERFACE (UI) UNTUK SISTEM PENILAIAN PESERTA MAGANG PERUMDA TIRTA MUSI PALEMBANG - Dhea Afnisyah Putri; Fathiyah Nopriani (CV. Denasya Smart Publisher, 2024)
The management and assessment of internship participants are still done manually, namely by filling out paper forms which are then processed separately. This manual process results in various obstacles such as the potential for human error, delays in data processing, and difficulties in storing and managing assessment history. Digitalization of the internship assessment process is an urgent need for Perumda Tirta Musi Palembang. A website-based internship assessment system can be a solution that allows the entire assessment process to be carried out automatically and in an integrated manner. This system also allows for the availability of assessment history that is stored neatly and in a structured manner, which ultimately makes it easier for companies to select and evaluate prospective internship participants in the future. The results of the research are the design of a User Interface for the assessment system which is expected to increase efficiency, transparency, and accuracy in the internship assessment process. This design can be a reference for further development, making it easier for admins to manage assessment data, and assisting supervisors and interns in a more structured evaluation process.